The cell regularity effects on the compressive responses of additively manufactured Voronoi foams. (December 2019) - Duan, Yu; Du, Bing; Zhao, Xianhang; Hou, Naidan; Shi, Xiaopeng; Hou, Bing; Li, Yulong
Highlights: The cell regularity effects on the compressive responses of additively manufactured Voronoi foams are studied experimentally and numerically. Kelvin foams (regularity = 1.0) show obvious higher collapse stresses and elastic limits than random foams (regularity = 0.0–0.8). The layered deformation bands can be seen in Kelvin foams while random foams exhibit random localized deformations. Random foams may lower the plateau stresses compared to Kelvin foams due to their cell-wall tearing failures. The cell regularity ranging from 0.0 to 0.8 has no obvious influence on the mechanical properties of foams. Abstract: Recent development in additive manufacturing (AM) technique has led to advances in fabricating foams with desired internal structures. By using AM technique, we fabricate random foams (regularity = 0.0–0.8) and Kelvin foams (regularity = 1.0) with similar relative densities. The effects of cell regularity on the mechanical properties and deformation mechanisms of Voronoi foams are investigated experimentally and numerically. A series of quasi-static and dynamic compressive tests are performed and the strain distributions are obtained by the digital imaging correlation method. Experimental results indicate that random foams have lower collapse stresses and plateau stresses than Kelvin foams. It is due to that random foams show random localized deformations and cell-wall tearing failures while Kelvin foams exhibit layered deformation bands and no tearing failure. To decouple the two deformation and failure mechanisms affecting the Voronoi-foam mechanical properties, further numerical investigations without introducing tearing failure are carried out and random foams are found to have lower collapse stresses but similar plateau stresses with Kelvin foams. Therefore, it can be concluded that random foams have randomly-distributed localized deformations and thus can always mitigate the collapse stress, but may lower the plateau stress compared with Kelvin foams because of their cell-wall tearing failures. In addition, the cell regularity (0.0–0.8) has no significant influence on the mechanical properties of foams based on all experimental and numerical data. Graphical abstract: Image, graphical abstract